Integration of simulation for ergonomics assessment in operation control centre (railway industries) / Adib Zulfadhli Mohd Alias - Adib Zulfadhli, Mohd Alias (2019)
As human-machine interface grow more immersive and graphically-oriented, ergonomics assessment can be simulated with the integration of different design software to replicate real life operation. This can optimize the Operation Control Centre design thus reduce the construction cost and ensure the high comfort level during operation. This study will focus on the translation of the CAD/Revit model into simulation software, either directly or through the intermediate stage of rendering package. Complete CAD/Revit model can be used to generate simulation model by straight forward translation of the whole model or with the algorithms for optimization. Hence this simulation-based system can be used to verify the performance of ergonomics factor related to the operation processes. On top of that, this research also has generate the initial data of Rapid Upper Limb Analysis (RULA). Sample result of posture 3 which involving large movement cause higher RULA result which show the ergonomics assessment need to be further optimize.